Programa de humanização de um hospital público, geral, universitário de Belo Horizonte, Minas Gerais: a percepção dos trabalhadores da equipe de enfermagem da unidade pronto-socorro - Wilma Guimarães (2014)
Objective: To analyze the Humanization Program of a public universitary hospital general in the city of Belo Horizonte, Minas Gerais, from the perception of the Emergency Department Nursing Staff. Methodology: This is a qualitative, descriptive and exploratory study. Data collection was carried out through semi structured interviews, consisting of two parts: the first, with self-applied questions to characterize the respondents´ profile; the second, consisting of discursive questions related to the humanization (definition/concept, information/knowledge about the Humanization Program / National Humanization Policy), humanized assistance and humanized work. The participants were randomly selected, after stratification according the title/position (nurses, technicians and nursing assistants) and types of work contracts, respecting the inclusion and saturation criteria. 23 interviews were carried out, adopting the discursive questions qualitative analysis reference, supported by the Política Nacional de Humanização (PNH)/ National Humanization Policy (NHP) principles, directions and methods, structured from the framework of content thematic analysis proposed by Bardin (2007). The study was approved by the Minas Gerais Federal University Ethics Committee in Research (Comitê de Ética em Pesquisa da Universidade Federal de Minas Gerais), according the advice number 510.093, of 14-01-2014. Results: Most respondents were female, between 36-45 years old, married, live in Belo Horizonte and Greater BH and have finished high school. Regarding title-position in the Emergency Department, three are nurses; fifteen are technicians and five nursing assistants. The majority (44%) has worked in hospitals for 10-20 years; 65% are government workers; 52% work during the day and 31% work in another department. Those workers participant in the study showed understanding and definitions regarding humanization, immediately relating the word to health assistance. These workers attribute to humanized assistance the meaning of quality care, the provision of care according to the needs of the users that seek the service, which is a right of all. The meaning of humanized work was strongly associated to the specific conditions for the production of health work/care. They pointed out several aspects that prove that there are still shortcomings and gaps, inconsistent with the proposals of the Humanization Program/ Humaniza SUS (Programa de Humanização/Humaniza SUS). They realize that the disability or lack in meeting the workers needs and improvement in their working conditions have negative impact both in the absence and in the professionals quality of life/work. Among the suggestions for improvement and resolution of the problems encountered the highlights are: more financial investment in the Humanization Program/Humaniza SUS( Programa de Humanização/Humaniza SUS), managers support and adherence, improvement in communication and interpersonal relationships, workers´ health promotions, ombudsman for the workers, investments in the qualification, staff incorporation in the discussions and decision making and a more participatory management. Thus, the conclusion based on the statements and the studies carried out was that it is not possible to promote the change in the production of health without taking into account the different subjects involved and without the commitment and participation of all the involved players – users, workers and managers. For the humanization to become a blunt, understood and acknowledged reality before the whole community it cannot favor some sectors and workers from specific areas, or admit conflict of interests.